Effect and consequence of the rheological properties of nano Fe2O3-modified drilling muds in the Dibella oil field - Mahamadou, Abdoulaye seyni; Jun, Gu; Moctar, Maimouna Issa (Frontiers in Energy Research, 2024)
The development of supportable, cost-effective, and superior execution nanoparticles is one of the new examination points inside penetrating applications. The consideration of tailorable nanoparticles offers the chance to figure out water-based drilling fluids with upgraded properties, giving uncommon open doors in the energy, oil, gas, water, or framework enterprises. In waterbased Drilling Fluids (WBDF), Nano and micron materials are investigated to control their rheological properties and their influence. This paper aims to analyze the influence of Nano Fe 2 O 3 on the rheological behavior of drilling fluid muds under high temperatures and pressure.Additionally, we seek to identify the optimal concentration of iron oxide nanoparticles that maintain consistent rheology; we examined the interfering effects of shear rates and iron oxide nanoparticle temperature on the shear type of the Changed Depleting Liquid of the Dibella oil field to make the penetrating activity efficient, realistic, and skilled. We observe that as the temperature rises, the water-based Mud (WBM), Plastic Viscosity (PV), Yield Point (YP), and Gel Strength (Gs) decrease till the reject structure is disappointed. Therefore, we must proceed with our assessment using Nano Fe 2 O 3 to resolve the shortcomings of the slop framework. Six water-based mud cakes containing 0.5, 1, 1.5, 2, 2.5, and 3g. weight percent iron oxide nanoparticles (Fe 2 O 3 ) were prepared for this evaluation, The experimental outcomes revealed an optimal nanoparticle mixing of 2.5g weight percent, which resulted in a 13.8% reduction in the API filtrate volume and a 40% reduction in filter cake thickness, At 300 0 F temperatures and type 10.00 pressure, The results of our experiments consistently demonstrate a decrease of 14.77% in the Rheological properties of PV, YP, 10 seconds, and 10 minutes in the gel strength of carbon oxide nanoparticles. The YP-PV span is 2.7, and the Yield Strength is 11 lb/100ft 2 .